A review of micro-contact physics, materials, and failure mechanisms in direct-contact RF MEMS switches. (19th September 2016) - Basu, A; Adams, G G; McGruer, N E
Abstract: Direct contact, ohmic MEMS switches for RF applications have several advantages over other conventional switching devices. Advantages include lower insertion loss, higher isolation, and better switching figure-of-merit (cut-off frequency). The most important aspect of a direct-contact RF MEMS switch is the metal microcontact which can dictate the lifetime and reliability of the switch. Therefore, an understanding of contact reliability is essential for developing robust MEMS switches. This paper discusses and reviews the most important work done over the past couple of decades toward understanding ohmic micro-contacts. We initially discuss the contact mechanics and multi-physics models for studying Hertzian and multi-asperity contacts. We follow this with a discussion on models and experiments for studying adhesion. We then discuss experimental setups and the development of contact test stations by various groups for accelerated testing of microcontacts, as well as for analysis of contact reliability issues. Subsequently, we analyze a number of material transfer mechanisms in microcontacts under hot and cold switching conditions. We finally review the material properties that can help determine the selection of contact materials. A trade-off between contact resistance and high reliability is almost always necessary during selection of contact material; this paper discusses how the choice of materials can help address such trade-offs.